Medical Students’ Attitudes Toward Communication Skills Learning in Chitwan Medical College, Nepal - Piryani, Suneel; Piryani, Rano Mal; Deo, Gopendra Prasad (Journal of BP Koirala Institute of Health Sciences, 2020)
Introduction: Medical students’ attitude towards communication skills is crucial for curriculum planners, teachers and health professionals. Chitwan Medical College (CMC) is a private medical school admitting students mainly from the Nepal.Objective: To assess the attitudes of medical students towards learning communication skills.Methods: A cross-sectional study was conducted among third and fifth year medical (MBBS) undergraduates at Chitwan Medical College (CMC), Nepal in April 2018 using the 26-itemCommunication Skills Attitude Scale (CSAS) developed by Rees, Sheard, and Davies. Participants ‘age, sex, year of study, nationality, religion, relationship status, the occupation of father and mother, place of residence of a family, were noted. The CSAS scores were computed. Student’s t-test and ANOVA test were used to compare the scores among subgroups of participants.Results: The mean positive attitudes scale (PAS), negative attitudes scale (NAS) and overall CSAS scores were 51.77  5.21, 35.68  4.43, and 83.97  5.77 respectively. PAS score was statistically significantly higher among the respondents whose mothers were not in the health-related profession. Whereas NAS score was statistically significantly lower among females, self-rated outstanding students, and good self-reported written communication skills.Conclusion: Medical undergraduates had strong positive attitudes towards learning communication skills, but negative attitudes were also noted. Hence, faculty members need to change these attitudes through improving teaching and assessment strategies.